Perceptrón memoria de correlación multicapa para predecir la violencia sistemática contra la mujer por su pareja en la Sierra del Perú - Ponce Aruneri, María Estela (2018)
In this research shows that the correlation model memory multilayer perceptron to predict the type of violence experienced by women over 14 have ever joined or united, ordinarily resident in the houses surrounding the Women's Emergency Centers located in the sierra del Peru, as well as significant associations between certain parenting styles, family relationships and perceptions about gender roles, with the kind of violence exercised by the husband / partner. We use 1126 cases of women from the database provided by the Ministry of Women and Vulnerable Populations (MIMP); for which fourteen input variables were built, one relating to parenting style received, three family relationships, nine out of perceptions about gender roles and one referring to the geographical, seven output variables relate to the type of violence against women by their partner or ex-partner. For the design stage memory model and correlation perceptron network training apply the backpropagation algorithm, the activation function used in this case was sigmoidal (logistic), we calculated the mean square error to evaluate the error committed by the network in each pattern (observation), and finally generalized delta rule to change weights and thresholds. Two programs were developed in Matlab to implement the memory mapping model multilayer perceptron with one and two hidden layers. The model multilayer perceptron correlation memory with two hidden layers I provide better results, 80.34% of correct predictions, and shows that family violence and perceptions about gender roles are important factors in predicting the type of violence that women have ever joined or united by their partner, and reside in the sierra of Peru.